Quality of life of the population, connected with health, as the basis of formation of the human capital in Republik of Kazakhstan. - Mukhanova, G. К. (Journal of Economic Research & Business Administration, 2015)
Population-based studies related to health of the population and the definition of quality of life based on the SF-36 questionnaire, carried out in many countries of the world, in Kazakhstan, such a study was conducted for the first time. The aim of the present work was to study the quality of life of the population 6 regions. Method was used assess the quality of life of the population on the basis of the subjective perception of the individual (J.Ware, 1988). The basis of this technique is the questionnaire MOS SF-36, which consists of 36 questions for assessing quality of life, based on the health of eight scales. All were interviewed more than 4,000 people. The paper presents the results of a study of quality of life of women. Implementation of this methodology for studying the quality of life in Kazakhstan opens up new opportunities for integrated assessment of health status, satisfaction with various aspects of life that will develop programs to improve the quality of life, both the municipal and regional level, which in turn will contribute to the qualitative growth human capital.